Awareness About the Orthodontic Specialty: A Survey Study - Arslan, Z.; Elekdag-Turk, S. (Elsevier, 2024)
Background: This study aimed to examine how well patients can differentiate between orthodontists and dentists. Methods: Four hundred patients who applied to the Ondokuz May & imath;s University Faculty of Dentistry, Department of Oral and Maxillofacial Radiology between March and November of 2022 were queried regarding the difference between an orthodontist and a dentist via a face-to-face survey. The respondents were separated into the following two study groups: patients who had previously undergone orthodontic treatment and those who had not. Demographic data of the patients, such as age, sex, educational status, and monthly income, were also collected, and the effects of these factors on their doctor preferences were analyzed. Results: The vast majority of respondents ( > 85%) thought that a dentist should be an orthodontic specialist to provide orthodontic treatment. Seven percent of patients chose to receive orthodontic treatment from a dentist. Patients who chose an orthodontist for their treatment were predominantly female and had a high income and a higher level of education. Patients who had a history of orthodontic treatment were better aware of the profession of orthodontics than those who did not. Conclusions: The results indicated that the respondents did not fully understand the clear distinction between an orthodontist and a dentist. This outcome suggests that education concerning this issue is required. (c) 2023 World Federation of Orthodontists. Published by Elsevier Inc. All rights reserved.
Arslan, Zeynep/0009-0009-0957-7707
Keywords: Awareness; Dentist; Orthodontic Treatment; Orthodontist